2017
DOI: 10.1111/1467-9817.12104
|View full text |Cite
|
Sign up to set email alerts
|

The relation between orthographic processing and spelling in grade 1 French immersion children

Abstract: This study investigates the within-and cross-language relations between orthographic processing and spelling for children learning to read in languages that share the same Roman script: namely, English and French. We examined these relations in a group of 152 children attending grade 1 in a French immersion program. Measures of English and French lexical orthographic processing (e.g., dream-dreem; jaune-jeaune) as well as English and French spelling were administered. Control measures included nonverbal abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
(142 reference statements)
3
17
0
2
Order By: Relevance
“…This seems to suggest that although phonological skills play a dominant role in spelling (Cunningham, 2006; Share, 1999), depending on the learning condition, orthographic processing might have a stronger influence on spelling acquisition. Learners’ abilities to perceive, access, and manipulate orthographic representations and patterns play an important role in their spelling acquisition (Chung et al, 2018). Fostering early‐grade learners’ orthographic skills would, therefore, be recommended to enhance spelling instruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This seems to suggest that although phonological skills play a dominant role in spelling (Cunningham, 2006; Share, 1999), depending on the learning condition, orthographic processing might have a stronger influence on spelling acquisition. Learners’ abilities to perceive, access, and manipulate orthographic representations and patterns play an important role in their spelling acquisition (Chung et al, 2018). Fostering early‐grade learners’ orthographic skills would, therefore, be recommended to enhance spelling instruction.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies on orthographic learning and self‐teaching has consistently demonstrated the importance of phonological skills when learning to read and spell (i.e., Cunningham, 2006; Share, 1999). However, less research has focused on the role of orthographic processing in spelling acquisition (Chung, Chen, & Deacon, 2018).…”
Section: Learning To Spell and Orthographic Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…B. alphabetisch oder logographisch). Andererseits gibt es auch Universalien, die für alle Schriftsprachen Gültigkeit haben (Perfetti & Verhoeven, 2017a (Chung et al, 2017;Chung et al, 2018;Commissaire et al, 2014;Kahn-Horwitz et al, 2014;Kim & Piper, 2019;Kuo et al, 2016;Shakkour, 2014;Wawire & Kim, 2018). Dabei zeigen sich besonders auf der Ebe-ne der hierarchiehöheren Leseprozesse Transferleistungen, wenig erstaunlich, handelt es sich dabei doch um konzeptuelles Wissen wie die Hinzuziehung von Vorwissen, die Inferenzziehung oder die Aktivierung von Textformatwissen (vgl.…”
Section: Cross-linguistische Einflussfaktoren Beim Lesenlernenunclassified
“…For these learners, transfer occurs from a highly proficient L1 to a less proficient L2. However, recent studies have demonstrated cross-language transfer of metalinguistic skills from the L2 to L1, or in both directions in emerging bilinguals acquiring two languages simultaneously (e.g., Chen, Xu, Nguyen, Hong, & Wang, 2010;Chung, Chen, & Deacon, 2018a). To expand the scope of the transfer facilitation model, Chung, Chen, and Geva (2018b) proposes an interactive framework, which identifies key factors that influence transfer in both directions in bilingual learners of different levels of proficiency.…”
mentioning
confidence: 99%